METODOLOGI FILSAFAT SEBAGAI PENDEKATAN STUDI ISLAM - Nuthpaturahman Nuthpaturahman (Jurnal Ilmiah Ilmu Pendidikan dan Kedakwahan, 2023)
Islam as a true guide for all its followers encompasses various dimensions of life. To read Islam in every aspect of life, the appropriate approach is needed to interpret it. One of the approaches that can be used is the philosophical approach that seeks to find universal conclusions by discussing the essence or nature of something. With this philosophical approach, Islam will not only be seen as a tradition, but Islam will also appear to be true in essence. Philosophy can relate to religion in various ways: as religion itself, a servant of religion, an opening for religion, a study of reasoning in religious thought, or an analytical device for religion. In the Islamic philosophy tradition, there are three methodological approaches to understanding religion: based on texts (bayani), based on direct experience of the spiritual reality of religion (irfani), and based on logical reasoning (burhani).